PENGARUH ONLINE COSTUMER REVIEW DAN LAYANAN CASH ON DELIVERY TERHADAP KEPUTUSAN PEMBELIAN DI MARKETPLACE SHOPEE - Marlina Tresnasih (JISMA: Jurnal Ilmu Sosial, Manajemen, dan Akuntansi, 2022)
The purpose of this research is to find out, firstly online customer reviews, COD services, and consumer purchasing decisions on Shopee marketplace users in Tasikmalaya City are in the very good category, secondly the influence of online customer reviews and cash on delivery (COD) services simultaneously on purchasing decisions in the marketplace. Shopee, and the third effect of online customer review and cash on delivery (COD) services partially on purchasing decisions on the Shopee marketplace. The method used in this study is a quantitative method with a survey approach. The results of the study show that online customer reviews, COD services, and consumer purchasing decisions on Shopee marketplace users in Tasikmalaya City are in the very good category. There is a simultaneous significant effect of online customer review and COD services on purchasing decisions for Shopee marketplace users in Tasikmalaya City. There is a partially significant influence online customer review on purchasing decisions on Shopee marketplace users in Tasikmalaya City. There is a partial significant effect of COD services on purchasing decisions for Shopee marketplace users in Tasikmalaya City.